1) y=1/4x^4-3/2x^2+2x
2) y=1/4x^4+1/3x^3-x^2
3) y=x^3+x^2-x
Thanks a lot
EDIT: nvm- figured it.
what is ur problem u do not know how to factorize or u have a problem in factorizing, show some work I will solve the first one
$\displaystyle \displaystyle y = \frac{x^4}{4} - \frac{3x^2}{2} + 2x $
all terms contains x or a power of x so we will take x as a common factor
$\displaystyle \displaystyle y = (x)\left(\frac{x^4}{4x} - \frac{3x^2}{2x} + \frac{2x}{x} \right) $
$\displaystyle \displaystyle y = (x)\left(\frac{x^3}{4} - \frac{3x}{2} + \frac{2}{1} \right) $
end